Splenic peliosis associated with rupture in a renal transplant patient. Issue 661 (November 1980) - Parsons, M. A.; Platts, M.; Slater, D.; Fox, M.
Abstract : A patient is described who, 2 years after renal transplantation, presented as an acute abdominal emergency due to a ruptured spleen. Histologically this displayed peliosis.